Configuração identitária do enfermeiro no contexto da estratégia de saúde da família - Beatriz Santana Caçador (2012)
The present study aimed to understand the nurses social identity in the context of the Family Health Strategy (ESF) in a Health District in Belo Horizonte, with the assumption that the ideological and structural reorganization of the work process through the ESF had influenced the identity configuration of these nurses. The study was conducted with seven family health care teams in the city of Belo Horizonte, MG. The study subjects consisted of two groups: the core - seven nurses, and the side: seven community health agents, six practical nurses and four doctors, all working in family health team for at least five years, totaling twenty- four subjects. The study was approved by the UFMGs Ethics and Research Committee ( 0128.203.000-10) and the in the local Ethics and Research Committee of Belo Horizonte (PBH) (006.2012A). This is a qualitative research and for the data collection was used the semi-structured interview after the consent of the subjects and signing the inform consent (TCLE). For data analysis, we used the technique of content analysis in the light of Bardin (1977). The results were grouped into three dimensions, namely: Micropolitical Dimension that makes the analysis of the lived world of nurses, the Real and Virtual Social Identity and also Interpersonal Relationship and the Identity construction;Organizational Dimension which covers the progress and challenges of the ESF, and the Systemic Dimension in which he analyzes the Health Care Network (RAS) in Belo Horizonte, their strengths and weaknesses and the influence of this organizational arrangement in the daily practices of the ESF nurses. In the Micropolitical Dimension the data revealed that the world experienced by nurses of the ESF is marked by ambiguous situations in their daily work, transiting between greater autonomy of action and decision-making to impotence and lack of governance to transform realities and needs that they have identified. Nurses experience also feelings of pleasure considering the emancipatory possibilities of action that the ESF gives them, but they also feel anguish and suffering because of the little professional appreciation and recognition given to them by management. The nurses indicate that wages are not proportional to the load of responsibilities and demands that are impose to them. Their everyday life is characterized by the overload of different kinds of assignments, specific to the nurse or not, contributing to the ESF set of prescribed activities and the strategy not being priority in their work. Regarding to the Organizational Dimension, it was found that the structure of the health centers determines precarious working conditions that limit nurses' performance. The management determines inconsistent work processes with the logic of the ESF as is the case of the implementation of the Manchester's Protocol in the primary health care system (APS). Making the ESF work without providing conditions for its implementation can generate distortion in the logic of the working teams causing the user's protection by ESF rather than the emancipation of themselves as subjects. The imbalance of the spontaneous demand assistance strengthens the gap between the prescribed and real dimension of the ESF. Moreover, in the perspective of the ESF professionals, the nurse is the one who sets the tone and pace of work to the family health care team, reflecting the very identity of the strategy. The Systemic Dimension presents the RAS as an important device in the assistance's organization and that deserves a standout for being developed in a large capital, like Belo Horizonte. However, there are many challenges that must be overcome, like: the lack of continuity in care due to the bottleneck of secondary health care system, shortage of professionals for certain specialties and lack of services to assist some needs such as adolescent's drug abuse demands. Thus, the ESF professionals identify demands that are repressed, which compromises the resolution of care starts in APS. Given the structural weaknesses that ESF presents and compromise the quality of nursing work, it is notice that this professional recognizes its responsibilities in ESF, understands the need to change the logic of health interventions, but did not find enablers conditions to perform these transformations. The ESF nurses struggle, in their everyday, to be EFS's nurses and the distance between the prescribed and real in their professional endeavors generates feelings of grief, frustration and anguish. An alternative suggested by the nuclear and secondary subjects of this research to minimize this framework is the deployment of Support Teams of nurses in the health centers that would be responsible for the demands of the unit, enabling ESF's nurses to perform their duties within the ESF. The study allowed us to understand the reality experienced by nurses in the ESF, identify the singularities of this scenario and analyze their identity. Furthermore, it was possible to outline elements relate to complex forms of being and the doing of the nurses through which identity, training and work are related. Finally, the study revealed the interfaces between organizational arrangements and the identity configuration of the nurse in the ESF.